Assessment of water quality in temperate-plain streams (Argentina, South America) using a multiple approach - Ocón, Carolina (2012)
We assessed the water quality in two pampean lotic systems (Argentina), the Juan Blanco and Buñirigo streams, subjected to different land uses (i. e., the UNESCO Biosphere Nature Reserve versus industry and agriculture, respectively) through measurements of physicochemical data and the structural parameters of the macroinvertebrate assemblages in addition to ecotoxicological analyses. The objective was to identify the degree of ecological impairment in adversely affected areas and the consequent effects on the biota. The results obtained allowed the establishment of different water-quality classes within the study area. According to the indices applied, the downstream zone of the Buñirigo stream was categorized as moderately polluted on the basis of losses of sensitive benthic species or changes in their abundance. Likewise, acute ecotoxicological bioassays demonstrated that the water from this site had lethal effects on Caenis nemoralis (Ephemeroptera: Caenidae) larvae. This sampling point also exhibited relevant physicochemical features, such as high water conductivity and nutrient levels as well as low contents of dissolved oxygen.